Frequency of Anti Hepatitis C Virus in Eye Surgery Patients at Tertiary Referral Center LUMHS - Ashok Kumar Narsani, Mahesh Kumar, Shafi Muhammad Jatoi (Pakistan Journal of Ophthalmology, 2009)
Purpose: To determine the incidence of anti-hepatitis C Virus in patients undergoing eye surgery. Material and Method: The study was conducted in the Department of Ophthalmology Liaquat University of Medical and Health Sciences Jamshoro from July 2007 to June 2008. In this study evaluation of 1128 patients of various ages under going eye surgeries and were unaware of hepatitis C infection were included in this study. Each patients was serologically screened by rapid chromatography immunoassay for qualitative detection of antibodies for Hepatitis C before surgery. Result: Five hundred forty four (48.22%) patients were male and 584 (51.77%) were female. Large number of patients were in 4th and 5th decade of life in both sexes. Of these 1128 patients, 334 (29.60%) were serologically positive for hepatitis C antibodies. Majority of them were male (54.80%) with male to female ratio of 1.21:1. Conclusion: The incidence of hepatitis C antibodies positive is higher in our population. There fore it is mendatory to screen every patient for hepatitis C and B before any surgical procedure. The surgeon and health care professional should protect themselves. The used infected material should be destroyed properly.